Manutenção da qualidade do feijão carioca sob armazenamento em atmosfera controlada - Soares, Tábata Zingano Bischoff (2019)
The bean (Phaseolus vulgaris L.) is an important legume, especially for developing countries, due to its high nutritional values of proteins, carbohydrates, minerals such as iron, potassium, and vitamins. In order to maintain the physiological quality of the bean seeds and the technological quality in the bean grains for prolonged periods, it is necessary to employ suitable techniques and controlled conditions in storage, in which water content of the product, relative humidity of the air, temperature, and partial pressure of the storage gases are the critical and indispensable parameters that can influence such characteristics. In this context, the use of modified atmosphere with low partial pressure of oxygen and high partial pressure of carbon dioxide can be an alternative to prolong the quality of the product. Due to the need for research investigating controlled atmosphere for seeds and bean grains, the first part of this work (Article 1) aimed at evaluating the main changes in the quality of bean seeds. In order to evaluate such alterations, analyses were carried out concerning water content, germination percentage, accelerated aging, emergence velocity index, seedling size, and tetrazolium. Following this study (Article 2), results were presented on to the technological quality of the bean grains, investigating parameters of water content, respiration, color, hydration capacity, cooking time, texture, total soluble solids, titratable acidity, tannins, antioxidant capacity, and peroxidase activity. The storage occurred at a temperature of 20 oC, with different partial pressures of carbon dioxide (3, 6 and 9 kPa) at a fixed oxygen rate (1.5 kPa), in different environments, ambient relative humidity and relative humidity 70±10% of the air. The analyzes were performed when the product arrived at the laboratory (control), immediately after storage and after 7 days of storage (shelf life). The storage of seeds and grains was carried out for 6 months in hermetically sealed polyethylene chambers. In order to achieve the desired gas concentration, the partial gas pressures were obtained by diluting the O2 in the storage environment with N2 injection and subsequent injection of CO2 from high pressure cylinders until reaching the pre-set level in the treatment. The experiment was conducted in a completely randomized complete factorial design, with 4 replicates for each treatment. Both ANOVA and Tukey tests were performed at the 5% level of significance, for analysis of variance and comparison of means, respectively. After such analyzes, only for the seed testing, the results were subjected to multivariate analysis by Pearson's linear correlation. Storage under controlled atmosphere, at high partial pressure of CO2 (9 kPa) influenced the seeds positively, preserving the integrity of the cell membranes, allowing them to remain with high germination and vigor. This information is confirmed by the high germination index (98.26%), average shoot length (12.61 cm), and tetrazolium (97%) levels presented. The storage of beans with high partial pressure of CO2 was important for the preservation of quality, maintaining the characteristics of the product for 180 days. When the grains were stored with partial pressure of 9 kPa of CO2, there was reduction in respiration, reducing deterioration. Therefore, there was a reduction in cooking time of 29.14 to 22.60 minutes and better hydration, increase in a* and reduction of b * (9.18 to 8.93), increase in L* (54.59), which represents greater clarity in the integument, under relative humidity 70±10%, and in shelf life the texture remained at the same levels, with increased antioxidant capacity post storage (2.55), reduction of shelf life tannins (171.34), and peroxidase activity remained low (654.94).